2018
DOI: 10.1136/jclinpath-2018-205216
|View full text |Cite
|
Sign up to set email alerts
|

p16

Abstract: The p16 gene belongs to INK4 family of genes and is made up of four members: p16INK4A, p15INK4B, p18INK4C and p19INK4D, all of which share biological properties, namely, inhibition of cell growth and tumour suppression. After p53, Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
76
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 24 publications
0
76
1
2
Order By: Relevance
“…The CDKN2A gene is a tumor suppressor gene located on chromosome 9 band 21.3; it encodes for several transcript variants, which differ in their first exons, and two major proteins: P16INK4a, which is a cyclin-dependent kinase inhibitor, and p14ARF, which binds the p53-stabilizing protein MDM2 ( 11 ). P16INK4a, through the inhibition of CDK4 and CDK6 (cyclin-dependent kinases 4 and 6), activates the retinoblastoma protein (RB), which blocks cellular cycle progression from phase G1 to phase S ( 12 ). CDKN2A mutations are commonly found in familial melanoma ( 13 ), and it has been hypothesized that alterations in cell cycle control genes are necessary for the acquisition of invasive potential and the transformation into invasive melanoma ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CDKN2A gene is a tumor suppressor gene located on chromosome 9 band 21.3; it encodes for several transcript variants, which differ in their first exons, and two major proteins: P16INK4a, which is a cyclin-dependent kinase inhibitor, and p14ARF, which binds the p53-stabilizing protein MDM2 ( 11 ). P16INK4a, through the inhibition of CDK4 and CDK6 (cyclin-dependent kinases 4 and 6), activates the retinoblastoma protein (RB), which blocks cellular cycle progression from phase G1 to phase S ( 12 ). CDKN2A mutations are commonly found in familial melanoma ( 13 ), and it has been hypothesized that alterations in cell cycle control genes are necessary for the acquisition of invasive potential and the transformation into invasive melanoma ( 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…CDKN2A mutations determine the alteration of protein P16INK4a expression. Many authors have demonstrated that P16INK4a immunohistochemical expression is preserved in benign nevi and is lost in CM ( 14 ), except for desmoplastic melanoma ( 12 ). While P16INK4a has been shown to be of little use when used alone; a panel encompassing P16INK4a, Ki67, and HMB45 is more effective in the differential diagnosis of melanocytic lesions in clinical practice ( 15 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, p16 mutations appear to be infrequent in prostate cancer (4); moreover, p16 overexpression in cancer has not yet been fully clarified. Certain types of tumour, such as melanoma, HPV-associated tumours, non-small cell lung cancer, mesothelioma and lymphoma exhibit diminished p16 protein levels (5)(6)(7), while in other tumours, including prostate cancer, the overexpression of wild-type or mutant p16 has been found (8,9). p16 overexpression is associated with tumour recurrence (10), and with a poor clinical course in patients with erythroblast transformation-specific-related gene (ERG)-negative prostate cancer (11); therefore, although p16 acts as a tumour suppressor gene, stress or oncogenic factors or alternative molecular events may overcome the role of p16 as a negative cell cycle regulator (12).…”
Section: Introductionmentioning
confidence: 99%
“…Due to the location of the tumor (vulva), we wondered if this expression was related to the presence of HPV infection. We didn't find HPV infection, but we know that p16 is not only associated with HPV infection but it's also a tumor suppressor gene implicated in several tumors [28].…”
Section: Resultsmentioning
confidence: 99%